CHARACTERIZATION OF ALTERNARIA BRASSICAE CAUSING ALTERNARIA BLIGHT OF RAPESEED- MUSTARD (BRASSICA JUNCEA L.) AND IT’S MANAGEMENT - DALEL SINGH; RAJENDRA PRASAD; SATGURU PRASAD YADAV (The Bioscan, 2014)
Ten fungicides, bio agent and nutrients ZnSO4+borex+sulphur were tested for their efficacy against Alternaria blight of rapeseed- mustard and was found to be effective in reducing disease intensity (19.06 and 20.7%) on leaves and disease intensity (5.83 and 15.1%) on pod and increase the yield (2.6tonne /ha and 1.1tonne /ha) during 2010-2011 and 2011-2012 respectively. The tested treatment spray of Pseudomonas fluorescens, mancozeb (0.2%) used as fungicidal check was the most effective to reduce the disease intensity (36.93 and 12.9%) on leaves, 14.93 and 12.2% on pod and increase the yield during 2010-2011 and 2011-2012, respectively. So ZnSO4+borex+sulphur and bio agents of pseudomonas fluorescence were recommended for management of Alternaria blight of rapeseed- mustard disease.